Comparison of procurement performance of rural transport infrastucture project and construction of large bridge on upazila & union Roads project in LGED - Yazdani, Md. Golam (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2013.